Los desastres de la guerra: el relato de Malvinas en dos obras de historieta argentina contemporánea - Pablo Turnes; Laura Cristina Fernández (Nuevo mundo - Mundos Nuevos, 2019)
This article aims to trace the way in which the Malvinas War has been treated and told in comics, within a broader framework that has to do with the historical narrative in comics of the last military dictatorship (1976-1983). That is to say, a process of progressive detachment that made Malvinas become something in itself, beyond the context that had given rise to it. In this sense, comics were part of a general process that initially highlighted this act as the final crime of the dictatorship, and which was originally proposed as the cornerstone of a democratic refoundation in Argentina. However, it would later turn into a warlike military narrative in opposition to post-dictatorial political discourse and against a good part of public opinion. Taking this in account, we mean to take to contemporary graphic novels – Malvinas: El cielo es de los Halcones (2015-2017) and Tortas fritas de polenta (2013) –, to assert the tensions and changes around the Malvinas issue that have taken place in the latter years.